Penguatan Profil Pelajar Pancasila Melalui Projek Event Organizer (EO) di SMKN 1 Surakarta - Francisca Poppy Chrisyunianti Dewi (Jurnal Indonesia Sosial Teknologi, 2023)
This article examines business opportunities in the field of event organizers or event organizers that can be done by anyone. The narrow employment opportunities in Indonesia are not proportional to the increasing number of SMK and Bachelor graduates every year. The government's ability to create jobs in the country has been unable to provide space for vocational school graduates and recent graduates to work. Opportunities are still open to build new fields in the field of entrepreneurship, including the event management service sector or event organizer. Event organizer services or also known as EOs are a business sector that provides opportunities for effective job creation for the community, especially for vocational school graduates and college graduates so that they do not have to compete to find work but instead open up opportunities to create their own jobs as well as for others. . Starting a business in the EO field is not as difficult as people imagine. In this article the emphasis is on project-based learning which is realized in making EO at SMKN 1 Surakarta as a form of our efforts as educators in vocational schools so that graduates of SMK N 1 Surakarta have qualified skills in an EO so that in the future they are able to compete in the world of work, as well as a manifestation of The Pancasila Student Profile Strengthening Project is to provide opportunities for students to learn in informal situations, flexible learning structures, more interactive learning activities, and also be directly involved with the surrounding environment to strengthen various competencies